Can mutation‐mediated effects occurring early in development cause long‐term seizure susceptibility in genetic generalized epilepsies?. (16th April 2018) - Reid, Christopher Alan; Rollo, Ben; Petrou, Steven; Berkovic, Samuel F.
Summary: Epilepsy has a strong genetic component, with an ever‐increasing number of disease‐causing genes being discovered. Most epilepsy‐causing mutations are germ line and thus present from conception. These mutations are therefore well positioned to have a deleterious impact during early development. Here we review studies that investigate the role of genetic lesions within the early developmental window, specifically focusing on genetic generalized epilepsy (GGE). Literature on the potential pathogenic role of sub‐mesoscopic structural changes in GGE is also reviewed. Evidence from rodent models of genetic epilepsy support the idea that functional and structural changes can occur in early development, leading to altered seizure susceptibility into adulthood. Both animal and human studies suggest that sub‐mesoscopic structural changes occur in GGE. The existence of sub‐mesoscopic structural changes prior to seizure onset may act as biomarkers of excitability in genetic epilepsies. We also propose that presymptomatic treatment may be essential for limiting the long‐term consequences of disease‐causing mutations in genetic epilepsies.